Healthcare as a Stress Test for Circular Economy Theory: Institutional Constraints, Resilience Trade-offs, and Policy Design - Gianpaolo Tomaselli (Journal of Circular Economy, 2026)
The healthcare sector is increasingly gaining consideration within sustainability debates, yet it remains under-represented in the dominant circular economy literature, which continues to focus primarily on manufacturing, waste management, and industrial production systems. This perspective paper examines healthcare as a stress test for circular economy theory. It argues that mainstream circular economy models often assume predictable, controllable material loops, whereas hospitals operate under conditions of clinical risk, sterility, redundancy, and regulatory constraint. The paper advances a governance-oriented critique of circularity in healthcare and identifies procurement reform, modular design, and life-cycle-based policy instruments as necessary conditions for transition. Healthcare exists to protect human health. Yet health systems are environmentally intensive institutions that consume large quantities of energy, water, plastics, chemicals, and single-use products while generating complex hazardous and non-hazardous waste streams. This environmental footprint alone justifies greater attention within sustainability policy, but the significance of healthcare for circular economy debates runs deeper than impact accounting. If circular economy is to function as an operational framework for reorganizing production and consumption, it must prove that it can operate not only in relatively controllable industrial settings but also in complex public-service systems where safety, continuity, and ethical obligation constrain experimentation. Hospitals are therefore not simply another sector in need of circular solutions; they are a demanding test case for the conceptual robustness of circular economy itself.